Sulfur based Composite Cathode Materials for Rechargeable Lithium Batteries - Zhang, Yongguang (2013)
Lithium-ion batteries are leading the path for the power sources for various portable applications, such as laptops and cellular phones, which is due to their relatively high energy density, stable and long cycle life. However, the cost, safety and toxicity issues are restricting the wider application of early generations of lithium-ion batteries. Recently, cheaper and less toxic cathode materials, such as LiFePO₄ and a wide range of derivatives of LiMn₂O₄, have been successfully developed and commercialized. Furthermore, cathode material candidates, such as LiCoPO₄, which present a high redox potential at approximately 4.8 V versus Li⁺/Li, have received attention and are being investigated. However, the theoretical capacity of all of these materials is below 170 mAh g⁻¹, which cannot fully satisfy the requirements of large scale applications, such as hybrid electric vehicles and electric vehicles. Therefore, alternative high energy density and inexpensive cathode materials are needed to make lithium batteries more practical and economically feasible.